The Role of Teacher's Pedagogic Competence in Cultivating Character Based on Scientific Learning in Elementary Schools: Peran Kompetensi Pedagogik Guru Dalam Penanaman Karakter Berbasis Pembelajaran Saintifik di Sekolah Dasar - Siti Mukhlisah; Nurdyansyah Nurdyansyah (Academia Open, 2022)
The role of teacher pedagogical competence in character building is the teacher's ability to design and implement learning that educates and is adapted to existing character values, and can direct the potential of students and evaluate learning. The purpose of this study 1). Analyzing the role of teacher pedagogical competence in character building based on scientific learning at SD Muhammadiyah 2 Tulangan, 2) Analyzing what factors support and hinder the cultivation of scientific-based character. This study uses qualitative research with descriptive methods. The research subjects were class III homeroom teachers, principals of SD Muhammadiyah 2 Tulangan and administrative staff. Data collection techniques using 1) Observation 2) Interview 3) Documentation. While the data analysis technique used the data triangulation technique. ,and has been made with a variety of techniques and methods that are interesting and fun. 2) Factors that influence character building in SD Muhammadiyah Tulangan are internal and external factors, namely the collaboration between teachers and parents. Highlights: Teacher pedagogical competence plays a crucial role in character building through adaptable and value-based learning. Factors influencing character building include internal and external elements, with collaboration between teachers and parents being vital. This study utilizes qualitative research with descriptive methods, employing observation, interviews, and documentation for data collection and triangulation. Keywords: Teacher pedagogical competence, Character building, Scientific learning, Qualitative research, Data triangulation